Observation of a mixed-sex, mixed-species aggregation of velvet ants, genus Timulla Ashmead, 1899 (Hymenoptera: Mutillidae) in the Brazilian Amazon, Roraima, with a new synonymy - Bartholomay, Pedro R.; Waldren, George C.; Oliveira, Marcio L. (Zootaxa, 2017)
An aggregation of two males of Timulla bitaeniata (Spinola, 1841), three single males T. rufogastra (Lepeletier, 1845) and another two males T. rufogastra (Lepeletier, 1845) in copula with two females of T. eriphyla Mickel, 1938 is documented, described and discussed. A new synonymy is proposed for Mutilla rufogastra Lepeletier de Saint-Fargeau, 1845 [=Timulla (Timulla) eriphyla Mickel, 1938, syn. nov.] based on the mating pairs.